How to open and operate a restaurant / Arthur L Meyer, Jon M Vann - Meyer, Arthur L
The restaurant business is both an established field and also an evolving one. Today more people eat out, having less time to cook at home. With the advent of the celebrity chef, many people are interested in trying new and different foods. The expansive cable television networks provide entertainment in the form of reality shows revolving around winning money to open a dream restaurant or be top chef. The globalization of food distribution allows people everywhere to become familiar with ingredients never before available, stimulating their interest in food as more than sustenance. Dining out becomes entertainment as well as filling the need for nourishment. With over 80 combined years of cooking experience, Meyer and Vann have seen the trials of opening and running restaurants--those they have worked in and those they have designed and helped to open.